2008
DOI: 10.1016/j.meatsci.2007.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between beef consumer tenderness perception and Warner–Bratzler shear force

Abstract: The aim of this study was to determine consumer ability to discern different levels of beef tenderness established by Warner-Bratzler shear (WBs). A panel of 220 people evaluated 60 samples of longissimus thoracis using a 5-point intensity scale (1: very tough; 5: very tender). Samples differed for commercial category, breed of animals and ageing length of meat. Shear force was measured by Instron equipped with a Warner-Bratzler device on 1.27 cm diameter cores. Correlation coefficient of WBs measurements with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
1
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(175 citation statements)
references
References 13 publications
3
139
1
15
Order By: Relevance
“…Destefanis et al (2008) reported that beef with WBS values higher than 5.37 kg and lower than 4.37 kg were perceived by most panellists as tough and tender, respectively. In this case, 62.30% of the consumers were able to distinguish tough from intermediate and tender meat.…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%
“…Destefanis et al (2008) reported that beef with WBS values higher than 5.37 kg and lower than 4.37 kg were perceived by most panellists as tough and tender, respectively. In this case, 62.30% of the consumers were able to distinguish tough from intermediate and tender meat.…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%
“…Consumers also attach great attention to the texture and tenderness of the meat (Purchas, 1990;Martinez-Cerezo, 2005).Tenderness is the primary determinant of eating quality and acceptability of meat (Voges et al, 2007;Destefanis et al, 2008). In most studies, meat tenderness has been evaluated instrumentally using the Warner-Bratzler shear method, which gives the best correlation with sensory panel scores for tenderness within muscles (Destefanis et al, 2008;Schönfeldt and Strydom, 2011). Perry et al (2001) reported that a shear force below 4 kg (40 N) is what equates to meat with an acceptable level of tenderness in Australian markets.…”
Section: Meat Qualitymentioning
confidence: 99%
“…Tenderness of meat is the most important quality distinguishing feature of meat in consumer evaluation [Koohmaraie, 1994[Koohmaraie, , 1996Boleman et al, 1995;Miller et al, 2001; Destefanis et al, 2008;Zork et al, 2009]. The problem of tenderness concerns mostly beef which requires at least 14 days of storage in cooling conditions to obtain the fi nal tenderness, while pork requires 5-7 days, and lamb 7-10 days .…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are willing to pay higher prices for beef which has guaranteed appropriate tenderness [Boleman et al, 1995[Boleman et al, , 1997Lusk et al, 2001;Shackelford et al, 2001;Feldkamp et al, 2005]. Various pre-slaughter and post-slaughter factors and their mutual effects infl uence tenderness of meat [Destefanis et al, 2008]. The most important pre-slaughter factors include: age, species, sex, breed, feeding of animals, degree of stress prior to slaughter, etc.…”
Section: Introductionmentioning
confidence: 99%